Biofungicidal Activity of Extract Sangket (Basilicum polystachyon (L.) Moench) Leaves to the Growth of Aspergillus flavus. - Sholikhah, Siti Lu'luatus; Ratnasari, Evie (LenteraBio : Berkala Ilmiah Biologi, 2022)
Aspergillus flavus is fungi that contaminate foodstuffs, especially grains. One way to inhibit the growth of these fungi is with biofungicide. Sangket (Basilicum polystachyon (L.) Moench) leaves contain compounds alkaloids, saponins, glycosides, flavonoids, and tannins that have the potential as biofungicide. The research aims are to know the biofungicide activity of sangket leaf extract and the optimal concentration on inhibiting the growth of Aspergillus flavus. The study implemented a Complete Randomized Design (CRD) with four replications. The concentrations used including: 10%, 20%, 30%, 40%, 50%, as well as positive controls using synthetic fungicides propinep 70% and negative control with aquades. Testing for antifungal activity using dilution method. The parameters measured are in the form of colony diameter to calculate the percentage of fungal inhibition. Analysis of data used one way ANOVA and continued with the Duncan test. The results stated that extract of sangket (Basilicum polystacyon (L.) Moench) leaves has biofungicide activity against the growth of Aspergillus flavus and the optimal concentration in inhibiting the growth of Aspergillus flavus is a concentration of 50%. The average diameter of the colony is 2.60 ± 0.42 cm and the average inhibitory percentage is 63.25 ± 6.31%.